I Can Has Supercomputer? A Novel Approach to Teaching Parallel and Distributed Computing Concepts Using a Meme-Based Programming Language - Richie, David A.; Ross, James A. (2017 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2017)
A novel approach is presented to teach the parallel and distributed computing concepts of synchronization and remote memory access. The single program multiple data (SPMD) partitioned global address space (PGAS) model presented in this paper uses a procedural programming language appealing to undergraduate students. We propose that the amusing nature of the approach may engender creativity and interest using these concepts later in more sober environments. Specifically, we implement parallel extensions to LOLCODE within a source-to-source compiler sufficient for the development of parallel and distributed algorithms normally implemented using conventional high-performance computing languages and APIs.